Accounting as a Tool of Power: A Critical Analysis of Financial Control Practices in Nonprofit Organizations - Moridu, Irwan (Dhana, 2025)
This study aims to analyze the role of accounting as a tool of power in nonprofit organizations, focusing on financial control practices used to legitimize the organization's existence and influence stakeholder relationships. In the context of nonprofit organizations, accounting serves not only as a means of recording transactions but also as an instrument of power that influences strategic decision-making and fund management. Accounting practices are often used to establish organizational legitimacy, manage relationships with donors, and ensure that funds are used in accordance with established objectives. This study found that transparent and accurate financial reporting plays a crucial role in legitimizing the organization's existence in the eyes of donors and the public. However, external pressure from donors and boards can encourage financial reporting manipulation practices, aimed at improving the organization's image. On the other hand, external audits serve to maintain transparency and accountability, although challenges related to weak internal controls remain a significant problem. These findings emphasize the importance of strengthening internal controls and more effective accounting systems to prevent financial manipulation and increase transparency in the management of nonprofit funds.